The Role of Community-Based Tourism in Sustainable Tourism Development in Central Maluku - Farida Mony; Achmad Zaky Marasabessy; Jusuf Sahupala; Agung K. Henaulu (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Central Maluku Regency has great potential to develop as a tourism destination, due to its abundant natural and cultural riches. With increasing awareness of the importance of sustainability in the tourism sector, community-based tourism (CBT) is a promising approach. Using a qualitative approach, this study explores how local communities can contribute to the management of natural and cultural resources, while simultaneously improving the economic well-being of the community. A systematic SWOT analysis, with strengths and weaknesses as internal environmental factors and opportunities and threats as external environmental factors, serves as a useful resource for decision-making in tourism management. Several significant findings that demonstrate the positive impacts and challenges faced in implementing community-based tourism in sustainable tourism development in Central Maluku include improving the local economy, empowering communities, and preserving culture and the environment. Active community participation in tourism development not only maintains environmental sustainability but also strengthens local cultural identity. It was also found that collaboration between the government, the private sector, and the community is crucial for creating a sustainable tourism model. This article is expected to provide insights for stakeholders in planning and implementing inclusive and sustainable tourism policies in Central Maluku Regency.